Penggunaan Media InteractiveFlat Panel (IFP) untuk Menciptakan Pembelajaran Interaktif Anak Usia Dini di KB Al Kholili - Putri Anggi Mailani; Desi Ismawati (STAI Al Mujtama Pamekasan, 2025)
This research discusses the use of interactive flat panel (IFP) media in early childhood learning at KB al kholili. The purpose of this research is to find out how the use of IFP can create effective and interactive learning to increase learning interestand ability of early childhood. Thid research method uses descriptive qualitative research with research subjects of teachers and early childhood at KB al kholili. Dara collection techniques through observation, interviews, and documentation. The results showed that the use of IFP can increase children’s learning interest, improve cognitive abilities, and improve social skills at KB al kholili. IFP also helps teachers create more interactive and enjoyable learning. This research concludes that IFP can be an effective alternative learning media to improve the quality of early childhood learning. Thus, the use of IFP can be one of the strategies to increase the interest in learning and the ability of early childhood at KB al kholili. This research is expected to contribute to the development of early childhood learning and improve the quality of education in Indonesia.